Analytical model of reactive transport processes with spatially variable coefficients. Issue 5 (May 2015) - Simpson, Matthew J.; Morrow, Liam C.
Abstract : Analytical solutions of partial differential equation (PDE) models describing reactive transport phenomena in saturated porous media are often used as screening tools to provide insight into contaminant fate and transport processes. While many practical modelling scenarios involve spatially variable coefficients, such as spatially variable flow velocity, v ( x ), or spatially variable decay rate, k ( x ), most analytical models deal with constant coefficients. Here we present a framework for constructing exact solutions of PDE models of reactive transport. Our approach is relevant for advection-dominant problems, and is based on a regular perturbation technique. We present a description of the solution technique for a range of one-dimensional scenarios involving constant and variable coefficients, and we show that the solutions compare well with numerical approximations. Our general approach applies to a range of initial conditions and various forms of v ( x ) and k ( x ). Instead of simply documenting specific solutions for particular cases, we present a symbolic worksheet, as supplementary material, which enables the solution to be evaluated for different choices of the initial condition, v ( x ) and k ( x ). We also discuss how the technique generalizes to apply to models of coupled multispecies reactive transport as well as higher dimensional problems.